An Ecosystem Leadership Model for the Media Industry in the Era of Technological Disruption - Hardy R Hermawan; Haryono Umar (Jurnal Komunikasi dan Bisnis, 2026)
Technological disruption has reshaped Indonesia’s media ecosystem through the dominance of digital platforms, the decline of legacy media, and growing regulatory uncertainty. Although prior studies address ecosystem leadership and dynamic capabilities separately, empirical models that operationalize ecosystem leadership in the media industry using fuzzy logic, particularly in emerging digital markets, remain limited. This study addresses this gap by developing an ecosystem leadership model using a qualitative approach integrated with fuzzy logic. Eight leadership indicators are examined: collaborative, orchestrative, inclusive, adaptive, visionary, transformational, legitimacy and trust, and sensemaking. Expert interviews were analyzed using fuzzy inference rules to transform subjective assessments into quantifiable leadership evaluations. The results show that legitimacy and trust, collaboration, and adaptability represent the strongest leadership foundations, while orchestration, inclusivity, and sensemaking remain underdeveloped. Analysis of dynamic capabilities indicates strong sensing and seizing capacities but moderate transforming capability, placing ecosystem leadership in the developing category. The fuzzy logic approach effectively captures leadership complexity under uncertainty. Practically, the findings provide guidance for media executives and policymakers to strengthen structural flexibility, inclusive governance, and orchestration mechanisms to enhance sustainability and resilience in digitally disrupted media ecosystems.